PUBLIC TRANSPORT OPTIONS FOR EAST ASIAN MEGA-CITIES - Parikesit, Danang (Jurnal Transportasi, 2008)
AbstractÂ This paper provides insights of the current state of public transport in East Asian Mega-cities, their characteristics that make them different with other public transport systems in other parts of the world. A combination of high percentage of public transport use, existence of para-transit, poor service quality to respond with high level of motorizations are some of the features of urban public transport in East Asian developing cities. Data from Tokyo, Shanghai, Seoul, Taipei, Ho Chi Minh City, Manila, Jakarta, and Bangkok are analyzed to develop a thorough understanding on the specific features of public transport in the East Asian Mega-cities. Several reform policies and strategies are proposed, including promoting public transport technology to shift the competition from costs to quality, fare integration, suitable financing options, and an appropriate implementation timing, as well as developing a public transport hierarchy to suit the increasing demand for urban mobility.Keywords: East Asia, urban area, public transport, reform strategy.